Kewaspadaan terhadap Kejadian Stroke pada Pasien Pasca Bedah Pintas Arteri Koroner - saidi, zaki; Widito, Sasmojo (RSUD Dr. Saiful Anwar Province of East Java, 2025)
Coronary artery bypass grafting (CABG) is a leading cause of iatrogenic stroke. According to the literature, the incidence of stroke following CABG ranges from 1.1% to 5.7%, with most strokes occurring within the first 48 hours after surgery. The risk of stroke after CABG is associated with a significantly higher mortality rate. A 62-year-old male patient with risk factors including hypertension and diabetes mellitus, as well as coronary artery disease 3 vessel disease left main disease (CAD3VD LM disease), was scheduled for CABG. Preoperative data indicated cardiomegaly on chest X-ray, normal carotid and extremity duplex ultrasonography, and echocardiography revealed a decreased ejection fraction and Regional Wall Motion Abnormality (RWMA). The CABG procedure lasted 7 hours and was performed using an on-pump technique, with cardiopulmonary bypass (CPB) time of 232 minutes and aortic clamp time of 123 minutes. Two days after the CABG, the patient developed complications in the form of an infarct stroke, which was confirmed by CT imaging. The stroke led to a prolonged hospitalization period, totaling 14 days. The mechanism of post-CABG stroke is divided into embolic and hypoperfusion processes, both influenced by various risk factors. In this patient, risk factors such as hypertension, type II Diabetes Mellitus, decreased ejection fraction, and perioperative factors such as prolonged CPB and aortic clamp times, along with aortic manipulation during the on-pump procedure, contributed to the increased risk of stroke.